DISTIBUSI BIVALVIA (MOLUSKA) DI DANAU SIPOGAS KABUPATEN ROKAN HULU PROVINSI RIAU - Naksar, Salman; Yolanda, Rofiza; Yolanda, Rofiza; Lubis, Riki Riharji; Purnama, Arief Anthonius (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aims of this study was to determine distribution of Bivalvia (Mollusca) in Sipogas Lake Rokan Hulu Regency, Riau Province. The study was conducted in November to December 2014 with survey method. Sample collected by using eckman dredge with purposive random sampling, with four stations. Results showed, 1 species was found, it was Corbicula javanica with a total number of 77 individuals. The density was ranged from 17.78 to 64 individuals/m2, with distribution patterns on pattern of grouped distribution.